ANALYSIS OF THE EFFECTS OF DEMOGRAPHIC VARIABLES AND CHARACTERISTICS OF THE FACEBOOK SOCIAL NETWORK ON PURCHASING - Vranješ, Marija; Jovičić, Dragoljub; Gašević, Dragana (International Journal of Economic Practice and Policy, 2020)
The aim of the paper is to analyze the effect of demographic features and Facebook usage characteristics on making a purchase. In this regard, descriptive statistics measures, reliability analysis, independent sample t -tests, one-factor and two-factor analysis of variance were used. The results of the study show that there are no statistically significant differences in gender or age regarding the purchase decision. Also, statistically significant differences in this regard are not detected in the case of variables concerning the characteristics of use of the social network Facebook (mode of access to the social network, length of use, frequency of logging in to the account, average time spent on the social network mentioned, and frequency of updating the account). A statistically significant result was observed only in the case of level of education. It has been found that people with the highest level of education (master / PhD) are more likely to make purchases (influenced by Facebook promotion), compared to persons with a bachelor`s degree and secondary education. In this regard, the research results suggest the management should focus marketing efforts towards people with the highest level of education. In addition, the problem associated with low levels of purchase of other groups of respondents has been identified, which requires further adaptation and improvement of promotional strategies.
Keywords: promotion on social networks; Facebook; purchasing